No Survival Advantage to Using Bevacizumab as First-Line Therapy for Glioblastoma - Kuznar, Wayne (MD Conference Express, 2013)
Data from a Phase 3 study indicate that the use of bevacizumab (BEV) in glioblastoma should not be extended to the first-line setting. Currently, BEV is approved by the United States Food and Drug Administration for the treatment of recurrent glioblastoma. This article discusses findings from the double-blind, placebo-controlled, randomized trial entitled Temozolomide and Radiation Therapy With or Without Bevacizumab in Treating Patients With Newly Diagnosed Glioblastoma [RTOG 0825; NCT00884741; Gilbert MR et al. J Clin Oncol 2013 (suppl; abstr 1)].